Hybrid subcarrier - optical spectrum code division multiplexing system with spectral direct decoding detection technique - Sahbudin, Ratna Kalos Zakiah (2010)
Today‟s telecommunication systems are expected to provide a reliable, affordable, flexible, scalable services and possess substantial information carrying capacity in order to meet the increasingly high user‟s expectation. There has been tremendous interest in applying hybrid multiplexing technique to fiber optic communication systems to enhance network flexibility and scalability. Optical spectrum code division multiplexing (OSCDM) is one of the multiplexing techniques that is becoming popular because of the flexibility in the allocation of channels, ability to operate asynchronously, enhanced privacy and increased capacity in bursty nature networks. On the other hand, subcarrier multiplexing (SCM) technique is able to enhance the channel data rate of OSCDM systems. The attractive feature of the current SCM technology is cost-effective as it provides a way to take advantage of the multi-gigahertz bandwidth of the fiber optics, using well-established microwave techniques for which components are commercially available. Hence, this thesis proposes a hybrid SCM and OSCDM (SCM-OSCDM) system for the purpose of combining the advantages of both techniques. This hybrid technique can increase the number of simultaneous users by increasing the SCM and/or the OSCDM codeword. The performance of the hybrid system strongly depends on the codes properties and the detection technique. The system utilizes a new unified code construction named Khazani-Syed (KS) code based on the Double Weight (DW) and Modified Double Weight (MDW) codes. KS code possesses an ideal in-phase cross correlation property, which led to the elimination of multiple access interference (MAI). The effect of MAI will degrade the system performance. Conventionally, MAI is reduced by using subtraction detection techniques. In this thesis, a new detection technique called Spectral Direct Decoding (SDD) is introduced. SDD technique requires less number of filters for the decoders as compared to the subtraction detection techniques and only filters out the non-overlapping spectral. Thus, eliminate the phase induced intensity noise (PIIN). The effectiveness of the new hybrid system with the proposed SDD technique has been verified and demonstrated through theoretical analysis, simulation and experimental work. The results show that the new hybrid system with the proposed SDD technique improves the performance than that using the conventional subtraction detection techniques. For example in theoretical analysis, at bit error rate (BER) of 10-9, the SDD technique provides an improvement in the total number of users over the AND subtraction by a factor of 4. The system capacity also shows an improvement of 17.734 Gbps for 20 users. Furthermore, the computer simulation results show that the transmission distance and bit rate per channel improve by 27% and 100%, respectively.